COMPENSATION, DISCIPLINE AND ORGANIZATIONAL CULTURE FOR EMPLOYEE PERFORMANCE (CASE STUDY AT SUNGAI PENUH CITY ENVIRONMENTAL OFFICE) - Wazirman Wazirman; Jecky Dambara; Eka Puspita HN (Jurnal Ekonomi, 2023)
This study aims to see the effect of (1) Compensation on the Performance of Sungai Penuh City Environmental Service Employees (2) Discipline on the Performance of Sungai Penuh City Environmental Service Employees (3) Organizational Culture on the Performance of Sungai Penuh City Environmental Agency Employees (4) Compensation, Discipline and Organizational Culture jointly affect the Performance of Sungai Penuh City Environmental Service Employees. The population in this study was all employees of the Sungai Penuh City Environmental Office as many as 38 people. And the technique of determining the number of samples taken as respondents using total sampling. The results of this study are that (1) Compensation has a significant positive influence on the Performance of Sungai Penuh City Environmental Agency Employees (2) Discipline has a positive influence on the Performance of Sungai Penuh City Environmental Agency Employees (3) Organizational Culture has a positive influence on the Performance of Sungai Penuh City Environmental Agency Employees (4) Compensation, Discipline and Organizational Culture together have a positive effect on Employee Performance Sungai Penuh City Environmental Office